The Changing Role of National Parliaments in the EU Enlargement - Ristova - Aasterud, Karolina (Macedonian Political Science Journal e-PP, 2016)
The paper analyzes the changing role and the impact of national parliaments in the EU Enlargement after the Lisbon Treaty of 2009. The main assertion is that, although the more active role of national parliaments may provide the enlargement process with greater democratic legitimacy in institutional and procedural terms, there are still some critical points that may have an adverse on the accession of new member states to the EU. Three such critical points are discussed. First, on the part of the EU, not enough efforts have been made to reflect upon the role of the EU national parliaments in the enlargement, as well as to provide for "parliamentary benchmarks" for the national parliaments of the candidate countries. Second, the enlargement strategies of the candidate countries continue to be "Brussels-focused" and "government-focused", thus underestimating the influence that EU national parliaments have acquired in the decision-making process regarding the accession of new member states to the EU. Third, the (obligatory) referendums on accession treaties may relativize not only the role of the EU national parliaments but also the overall effect of the EU accession criteria and conditionality logic in the Enlargement process.
Keywords: national parliaments, EU, Enlargement